2022
DOI: 10.1051/ro/2022113
|View full text |Cite
|
Sign up to set email alerts
|

Markdown pricing strategy under a dual-channel supply chain with strategic consumers

Abstract: This study investigates the markdown pricing strategies for a manufacturer and a retailer in a twoperiod dual-channel supply chain, where the manufacturer sells its products via its own direct channel and an independent retail channel to strategic consumers who may wait for markdowns. A two-period game is developed to systematically study the optimal regular prices and markdown prices under four cases, i.e., no markdown in both channels, markdown only in the direct channel, markdown only in the retail channel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Many scholars have also studied strategic consumers on the basis of a dual-channel system. Li et al [22] pointed out that with the increase in the proportion of short-sighted consumers, the price competition between a physical channel and a network channel under decentralized decision-making will become more intense, with the manufacturer dominating the competition at this time; in addition, the collusion between supply-chain members can make the prices of two channels reach high prices, with the retailer dominating the competition at this time. Cao and Huang [23] believed that if the number of strategic consumers in the market is small, and their influence on the supply chain is very small, manufacturers mainly consider the behaviours of retailers when making pricing decisions.…”
Section: Literature Review 21 Strategic Consumption Behavioursmentioning
confidence: 99%
See 4 more Smart Citations
“…Many scholars have also studied strategic consumers on the basis of a dual-channel system. Li et al [22] pointed out that with the increase in the proportion of short-sighted consumers, the price competition between a physical channel and a network channel under decentralized decision-making will become more intense, with the manufacturer dominating the competition at this time; in addition, the collusion between supply-chain members can make the prices of two channels reach high prices, with the retailer dominating the competition at this time. Cao and Huang [23] believed that if the number of strategic consumers in the market is small, and their influence on the supply chain is very small, manufacturers mainly consider the behaviours of retailers when making pricing decisions.…”
Section: Literature Review 21 Strategic Consumption Behavioursmentioning
confidence: 99%
“…We also found that existing research considering both factors mentioned above is rare. Close to the research in this paper is Li et al [22] research, which considers both shortsighted and strategic consumption behaviors in the dualchannel supply chain system. They divide the whole market demand into five parts according to the balance between the utility and valuation of products by strategic consumers, and derive different demand functions.…”
Section: Blockchain In the Supply Chainmentioning
confidence: 99%
See 3 more Smart Citations